항산화 효소가 첨가된 Percoll에 의해 분리한 돼지 정액의 동결-융해 능력 - 이경진; 이상희; 주선호; 김유진; 양진우; 이연주; 황보 용; 이승형; 이승태; 이은송; 박춘근; Kyung-Jin Lee; et al. (Journal of animal reproduction & biotechnology (Online), 2015)
The objective of this study was to evaluate the efficiency of sperm cryosurvival in boar sperm separated by Percoll containing antioxidant enzymes. The boar semen was collected into a pre-warmed (37℃) thermos bottle by gloved-hand method and was separated by 65% Percoll with superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) before freezing. The frozen sperm was thawed at 38.5℃ for 45 sec in water-bath for sperm characteristic analysis. The sperm were estimated with SYBR14/PI double staining for viability, FITC-PNA/PI double staining for acrosome reaction, Rhodamine123/PI double staining for mitochondrial integrity and were analyzed using flow cytometry. In results, sperm viability, acrosome reaction and mitochondrial integrity were improved in separated sperm groups compared with unseparated sperm by Percoll (UP) group. Especially, viability was significantly higher in sperm separated by Percoll containing 400 IU CAT group compared with other groups (P<0.05). And acrosome reaction was decreased in sperm separated by Percoll with 300 IU SOD, 400 IU CAT and 0.5 mM GSH groups compared with other groups, however, there were no significantly difference mitochondrial integrity among sperm separated by Percoll with antioxidant enzymes. In conclusion, we suggest that use of Percoll containing antioxidant enzymes for sperm separation will be beneficial for sperm cryopreservation in pigs.